1991
DOI: 10.1016/1010-7940(91)90143-8
|View full text |Cite
|
Sign up to set email alerts
|

The colon as oesophageal substitute in non-malignant disease *1Long-term clinical results and functional studies

Abstract: Between 1974 and 1987, we performed 18 left colonic interpositions for benign oesophageal disease: caustic lesions in 6 patients, undilatable reflux stenosis in 5, reoperative peptic strictures in 5, penetrating wound in 1 and iatrogenic stricture following oesophagogastric transection for bleeding in 1. Four patients were women. The mean age was 40 +/- 19 years. In 10 patients a left thoracotomy was used; in the other 8 a cervico-abdominal approach was employed. One patient died postoperatively from liver fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…14,19 Colonic conduits are reported to have active peristalsis, and this is presented as an explanation for their superior function as an esoph-ageal substitute compared with a passive gastric conduit. 30,31 Although peristalsis can be demonstrated immediately after surgery, 32 long-term emptying likely relies on gravity. 33 When the distal stomach is retained in the abdomen after a colon interposition with a cologastric anastomosis, the latter provides additional reservoir function.…”
Section: Commentmentioning
confidence: 99%
“…14,19 Colonic conduits are reported to have active peristalsis, and this is presented as an explanation for their superior function as an esoph-ageal substitute compared with a passive gastric conduit. 30,31 Although peristalsis can be demonstrated immediately after surgery, 32 long-term emptying likely relies on gravity. 33 When the distal stomach is retained in the abdomen after a colon interposition with a cologastric anastomosis, the latter provides additional reservoir function.…”
Section: Commentmentioning
confidence: 99%
“…Isolauri et al [20]showed that radionuclide transit of the colon graft for the esophagus was markedly slower than that of the normal esophagus and suggested that reconstruction with proximal cologastric anastomosis and a short intra-abdominal colon graft segment would be preferable. Paris et al [21]reported that solid radionuclide colonic transit findings in patients with a short transplant were similar to those observed in the normal esophagus. We also documented the usefulness of a short segment of colon following proximal gastrectomy [14].…”
Section: Discussionmentioning
confidence: 82%
“…De las opciones antes mencionadas la que tiene más popularidad entre los cirujanos es la coloplastía derecha, ya que requiere una movilización del mismo menos agresiva, con la ventaja de ser isoperistáltica por necesidad manteniendo en forma teórica una mejor función de deglución [11][12][13][14][15] .…”
Section: Discussionunclassified
“…Debido a que se ha visto que el colon ascendido tiene actividad peristáltica, el realizar el injerto de forma isoperistáltico, lograría tener una mejor función de deglución, sin embargo, cuando la prueba del clampeo de los vasos cólicos izquierdos no es satisfactoria se opta por la coloplastía anisoperistáltica pediculada en los vasos cólicos medios [11][12][13][14] .…”
Section: Discussionunclassified